Muslim marriage and non-marriage where religion and politics meet intimate life - McBrien, Julie 1974-; Moors, Annelies 1953- (Leuven University Press, 2023)
Perspectives and practices of couples in unconventional Muslim marriages. Unconventional Muslim marriages have been topics of heated public debate. Around the globe, religious scholars, policy makers, political actors, media personalities, and women's activists discuss, promote, or reject unregistered, transnational, interreligious and other boundary-crossing marriages. Couples entering into such marriages, however, often have different concerns from those publicly discussed. Based on ethnographic research in Europe, the Middle East, North Africa and Asia, the chapters of this volume examine couples' motivations for, aspirations about, and abilities to enter into these marriages. The contributions show the diverse ways in which such marriages are concluded, and inquire into how they are performed, authorized or contested as Muslim marriages. These marriages may challenge existing ties of belonging and transform boundaries between religious and other communities, but they may also, and sometimes simultaneously, reproduce and solidify them. Building on insights from different disciplines, both from the social sciences (anthropology, political science, gender and sexuality studies) and from the humanities (history, Islamic legal studies, religious studies), the authors address a wide range of controversial Muslim marriages (unregistered, interreligious, transnational, etc.), and include the views of religious scholars, state authorities, and political actors and activists, as well as the couples themselves, their families, and their wider social circle.
Keywords: Islam; Mischehe; Ehe; Islamic marriage customs and rites; Marriage / Religious aspects / Islam; Marriage (Islamic law); Interfaith marriage; Aufsatzsammlung